2004
DOI: 10.2320/matertrans.45.2245
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Grain Refinement on Thermal Stability of Metastable Austenitic Steel

Abstract: In martensitic steels, it is well known that a certain chemical driving force (about 180 MJ/m 3 ) is required to start martensitic transformation (Ms), and additional driving force has to be charged further to complete the transformation (Mf). In the case of metastable austenitic steels with Ms temperature at around room temperature, however, only the chemical driving force needed to start martensitic transformation has been stored at room temperature. Hence, the state of austenite is very unstable thermally… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
105
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 228 publications
(109 citation statements)
references
References 8 publications
4
105
0
Order By: Relevance
“…Takaki et al pointed out that as PAGS is reduced, the number of variants forming during martensitic transformation is reduced. [32] This agrees with current observations in martensitic steel. The number of packets per parent austenite grain is reduced with decreasing PAGS as well as the ratio d PAGS /d PS , which approaches unity.…”
Section: A Effect Of Thermal Cycling On Grain Substructuressupporting
confidence: 83%
See 1 more Smart Citation
“…Takaki et al pointed out that as PAGS is reduced, the number of variants forming during martensitic transformation is reduced. [32] This agrees with current observations in martensitic steel. The number of packets per parent austenite grain is reduced with decreasing PAGS as well as the ratio d PAGS /d PS , which approaches unity.…”
Section: A Effect Of Thermal Cycling On Grain Substructuressupporting
confidence: 83%
“…Takaki [32] explained austenite stabilization with refinement of grain size by the increasing difficulty of multivariant transformation. Unlike coarse grains in which multivariant blocks form to minimize the local shear distortion accompanied with the martensitic transformation, in fine PAGs, the relaxation of volume expansion is not enough and the elastic strain energy becomes large.…”
Section: E Influence Of Pags On Martensite Transformationmentioning
confidence: 99%
“…Additionally, the blocks transformed from the ultrafine-grained austenite tend to exhibit rather equiaxed morphology compared with those transformed from the coarse-grained austenite. Takaki et al 6) reported that the ultrafine-grained austenite with grain sizes smaller than 10 µm transformed to single variant martensite or single packet (variants of martensite with the identical habit plane) in an austenitic stainless steel. As shown in the EBSD orientation maps of Figs.…”
Section: +1mentioning
confidence: 99%
“…The high thermal stability of bulky polycrystalline austenite with ultrafine grains against martensitic transformation was also confirmed in an FeNi alloy 5) and an austenitic stainless steel. 6) In addition, it was reported that the crystallographic features, such as variant selection rule and orientation relationship, of martensite transformed from ultrafine-grained austenite were different from those transformed from coarse-grained austenite.…”
Section: Introductionmentioning
confidence: 99%
“…Since the martensitic transformation proceeds so as to accommodate anisotropic lattice displacement by forming several fine grains with different crystallographic orientations (variants), 12) the banded structure can be subdivided effectively and the anisotropy is reduced through the multi-variant transformation on cooling, even if the coarse austenite colonies have been formed during hot rolling after solidification. As a result, the recrystallized ferritic structure formed from such a martensitic structure is also expected to have crystallographic isotropy.…”
Section: Introductionmentioning
confidence: 99%